Validation of a novel non-hyperaemic index of coronary artery stenosis severity: the Resting Full-cycle Ratio (VALIDATE RFR) study - Svanerud, Johan; Ahn, Jung-Min; Jeremias, Allen; van 't Veer, Marcel; Gore, Ankita; Maehara, Akiko; Crowley, Aaron; Pijls, Nico H.J.; De Bruyne, Bernard; Johnson, Nils P.; Hennigan, Barry; Watkins, Stuart; et al. (EuroIntervention, 2018)
Randomised controlled trials have reported instantaneous wave-free ratio (iFR) to be non-inferior to fractional flow reserve (FFR) for major adverse cardiovascular events at one year; however, iFR is limited by sensitive landmarking of the pressure waveform, and the assumption that maximal flow and minimal resistance occur during a fixed period of diastole. We sought to validate the resting full-cycle ratio (RFR), a novel non-hyperaemic index of coronary stenosis severity based on unbiased identification of the lowest distal coronary pressure to aortic pressure ratio (Pd/Pa), independent of the ECG, landmark identification, and timing within the cardiac cycle. VALIDATE-RFR was a retrospective study designed to derive and validate the RFR. The primary endpoint was the agreement between RFR and iFR. RFR was retrospectively determined in 651 waveforms in which iFR was measured using a proprietary Philips/Volcano wire. RFR was highly correlated to iFR (R2=0.99, p<0.001), with a mean bias of -0.002 (95% limits of agreement -0.023 to 0.020). The diagnostic performance of RFR versus iFR was diagnostic accuracy 97.4%, sensitivity 98.2%, specificity 96.9%, positive predictive value 94.5%, negative predictive value 99.0%, area under the receiver operating characteristic curve of 0.996, and diagnostically equivalent within 1% (mean difference -0.002; 95% CI: -0.009 to 0.006, p=0.03). The RFR was detected outside diastole in 12.2% (341/2,790) of all cardiac cycles and 32.4% (167/516) of cardiac cycles in the right coronary artery where the sensitivity of iFR compared to FFR was lowest (40.6%). RFR is diagnostically equivalent to iFR but unbiased in its ability to detect the lowest Pd/Pa during the full cardiac cycle, potentially unmasking physiologically significant coronary stenoses that would be missed by assessment dedicated to specific segments of the cardiac cycle.